On the parametric elliptical variational-hemivariational inequality problem with applications. Issue 18 (12th December 2022) - Chang, Shih-sen; Salahuddin,; Wang, L.; Wen, C. F.
Abstract : The goal of this paper is to introduce a new class of parametric elliptical variational-hemivariational inequality problems together with parametric inverse problems. We show the existence of solution for parametric inverse problem and well-posedness of parametric elliptical variational-hemivariationl inequality problems. An implementation in nonlinear elasticity, we address the parametric inverse problem for a parametric frictional unilateral contact problem.